2016
DOI: 10.3892/ol.2016.5222
|View full text |Cite
|
Sign up to set email alerts
|

miR-219-5p inhibits proliferation and clonogenicity in chordoma cells and is associated with tumor recurrence

Abstract: Chordoma is a rare malignant bone tumor that is usually localized to the skull base, vertebral column and sacrum. The transcription factor brachyury, which is encoded by the T gene, has a critical role in the development and progression of chordoma, although the mechanisms underlying brachyury regulation remain unclear. The aim of the current study was to identify and characterize microRNAs (miRs) that regulate brachyury expression in chordoma. MicroRNAs that target brachyury were predicted using miRanda and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…3I and J . Previous studies have also included the use of a common control for mimics and inhibitor experiments ( 28 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…3I and J . Previous studies have also included the use of a common control for mimics and inhibitor experiments ( 28 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, published data have suggested that many other miRNAs may impact patient outcomes in spinal chordoma (7). Our future study will further evaluate the eligibility for adding other miRNAs (such as miR-219-5p and miR-31) into the miRscore model and assessed their effect on spinal chordoma prognosis (45,46). Finally, our study is a correlation study in nature.…”
Section: Limitationsmentioning
confidence: 98%
“…Besides the miRNAs described above, numerous others have been reported to be associated with the pathogenesis of chordoma. For example, Bayrak et al report an additional 53 dysregulated miRNAs in skull base chordoma compared to the biology of normal nucleus pulposus, and Wei et al demonstrate the chordomagenic effect of miRNA 219-5p expression and its association with poor prognosis by studying spinal and sacral chordomas [4,17].…”
Section: Reviewmentioning
confidence: 99%
“…Bayrak et al and Zou et al look at skull base and spinal chordomas [4,12,18]. Wei et al study both spinal and sacral chordomas [17]. Although miRNA 155 upregulation was studied to be associated with poorer prognosis of sacral chordoma by Osaka et al, an isolated study of the sacral chordoma’s molecular pathogenesis i.e., identification of certain miRNAs’ association with a specific oncogene, is lacking [8].…”
Section: Reviewmentioning
confidence: 99%